Behavioral Phenotypes for Childhood Obesity: 2017 Alan N. Epstein Research Award - Kral, Tanja V.E. (Physiol Behav, 2018)
The percentage of children in the United States with obesity has more than tripled since the 1970s. Despite considerable work in this area, there has been limited success in the long-term treatment and prevention of childhood obesity. In order for intervention approaches to be successful, it will be crucial to study individual variation and the underlying mechanisms that impact human ingestive behavior. Research in my laboratory has focused on identifying behavioral phenotypes for childhood obesity which may be used to develop targeted intervention approaches that are tailored to a child’s individual predisposition. This work has included studying select appetitive traits among weight-discordant siblings and unrelated children to elucidate potential differences in children’s ability to regulate short-term energy intake and susceptibility to eating in response to food cues in the environment. I am greatly honored to be the recipient of the 2017 Alan N. Epstein Research Award from the Society for the Study of Ingestive Behavior (SSIB). I want to acknowledge and express my sincere gratitude to my mentors and colleagues who have supported me and provided guidance throughout my research career and to my research team and students for their hard work on our studies.